Estigma relacionado à Tuberculose: aplicação da Escala Tuberculosis-Related Stigma - Lucenti, Laís Xavier de (Universidade Federal de São Carlos, 2023)
Tuberculosis is a serious public health problem worldwide, it is estimated that in 2021, in the world, 10.6 million people will develop TB and 1.4 million will die from the disease. There are factors that interfere with adherence to treatment, such as the length of treatment being six months, non-acceptance of the disease, resistance to follow-up at health units, incorrect use of medications, and social stigma. The objective of this study was to investigate the stigma associated with tuberculosis, from the perspectives of the community and the patient in relation to the disease. This is a cross-sectional study with a quantitative approach, carried out in the city of São Paulo, in Basic Health Units. The Tuberculosis-Related Stigma scale was applied to 69 individuals with pulmonary tuberculosis who had been on Directly Observed Treatment for more than 15 days. In the first stage of the study, we carried out a bibliographical survey to highlight the need to study tuberculosis and the stigma surrounding tuberculosis, and the second part of the study presents the statistical analysis of the collected data. The results indicate that of the 69 individuals, 46 (66.7%) agree that people prefer not to have someone with TB living in their neighborhood, 37 (53.6%) agree that the population keeps distance from people with TB and think that they cause disgust, 38 (55.1%) of the subjects agree that people do not want people with TB to play with their children, and do not want to talk to someone who has Tuberculosis, 29 (42.0%) agree that people with TB keeps distance from others to avoid transmission of the bacteria, 32 (46.4%) agree that people with TB feel hurt by the way others react when they know they have TB, and 29 (42.0%) strongly agree that people with TB choose carefully who they tell about their disease. The statistical analysis of data from the application of the scale shows that the scale measures the stigma associated with tuberculosis, which is associated with fear and prejudice.
Tuberculosis-Related Stigma: application of the Tuberculosis-Related Stigma Scale
Keywords: Cuidado à pessoa com tuberculose; Estigma social; Saúde Pública; Tuberculose; Care for people with tuberculosis; Social stigma; Public health; Tuberculosis; CIENCIAS DA SAUDE::ENFERMAGEM